Septin9 DNA methylation as a promising biomarker for cervical cancer - Qiaowen Bu; Xiping Luo; Lulu He; Jian Ma; Shaoyi He; Wen Lei; Weiping Zhou; Hua Deng; Yu Lin; Liang Zhang; Xiaoshan Hong (Taylor & Francis Group, 2023)
Aberrant Septin9 methylation in cervical cancer has been rarely studied. We aimed to identify its diagnostic value in cervical cancer using cervical scrapings, and its predictive potential in plasma for pelvic nodal metastasis of cervical cancer. The statuses of methylated Septin9 in fresh cervical lesions and cervical scrapings were first evaluated by using quantitative methylation-specific PCR. Subsequently, the relationship between Septin9 methylation in 113 plasma samples and pelvic nodal metastasis of cervical cancer was evaluated. Methylated Septin9 was detected in all cancerous tissues, but not in cervicitis. The degrees of Septin9 methylation increased with growing severity of cervical lesions in cervical scrapings. The sensitivity of methylated Septin9 was lower than that of cytology, while it yielded a high specificity and area under the curve in detecting high-grade squamous intraepithelial lesion or cervical cancer; and when Septin9 methylation combined with HPV16/18 genotyping, the sensitivity would increase from 70.42% to 82.39%. Plasma-based Septin9 methylation had a high discriminatory power in predicting pelvic nodal metastasis of cervical cancer, with an optimal specificity of 81.48%. In conclusion, we demonstrated methylated Septin9 to be an innovative diagnostic biomarker for cervical cancer and its non-invasive predictive potential in plasma for pelvic nodal metastasis of cervical cancer.Impact statement What is already known on this subject? The occurrence of cervical cancer is related to Septin9 methylation. In fresh specimens and cervical scrapings, we found the degrees of methylated Septin9 increased with growing severity of cervical lesions. Compared with HPV16/18 genotyping and cytological detection, Septin9 methylation had a better specificity and AUC in detecting ≥ HSIL. Furthermore, plasma-based Septin9 methylation also had a high specificity for pelvic lymphatic metastasis prediction. What the results of this study add? Methylation analysis of Septin9 indicated a similar sensitivity, specificity and AUC in detecting ≥ HSIL, relative to HPV16/18 genotyping. Compared with cytological method, Septin9 methylation also yielded a higher specificity and AUC in detecting ≥ HSIL. And we also found plasma-based Septin9 methylation had a high discriminatory power in predicting pelvic nodal metastasis of cervical cancer, with an optimal specificity of 81.48%; additionally an increasing sensitivity from 50% to nearly 80% was found when combined with SCCAg. What the implications are of these findings for clinical practice and/or further research? This study aimed to evaluate the relationship between Septin9 methylation and cervical cancer, and to explore the value of methylated Septin9 in the detection of cervical (pre)cancerous lesions. Moreover, we would explore plasma-based ctDNA biomarkers for pelvic lymphatic metastasis prediction of cervical cancer, to improve non-invasive predictive accuracy of pelvic nodal metastasis and reduce the complications caused by pelvic lymphadenectomy.